A fast thermal desorption unit for micro thermal desorption tubes, Part I: Development of the system and proof of concept measurements with hyper-fast gas chromatography - Chopra, Miriam D.; Menger, Florian A.; Duong, Benny; Wüst, Matthias; Boeker, Peter (Journal of Chromatography A, 2024)
A system consisting of a thermal desorption unit (TDU) and micro thermal desorption tubes (μTD-tubes, 1.4 mm I.D., 10mg Tenax TA) for fast desorption of analytes was developed for the efficient combination of hyper fast gas chromatography with thermal desorption. The fast desorption is achieved by a significantly reduced thermal mass compared to conventional thermal desorption tubes. Therefore, extremely fast heating and cooling cycles are possible. Proof of concept measurements combining the new setup with a flow-field thermal gradient gas chromatograph (FF-TG-GC) and FID detection show good precision and linearity with R2≥0.995 in the analysis of an n-alkane mix (C8-C20). Thermal desorption occurs within 12s. The impact of reduced μTD-tube dimensions on desorption time, full width at half maximum (FWHM), breakthrough volumes, tube flow rates ergo linear velocities, porosity and back pressure is discussed. •New micro thermal desorption tubes (μTD-tubes) for fast GC analysis.•Rapidly heatable and coolable thermal desorption unit for μTD-tube desorption.•Low thermal mass μTD-tubes and thermal desorption unit.•New application for flow field thermal gradient gas chromatography (FF-TG-GC).•Fast thermal desorption of n-alkanes within 12 s and a cycle time of 90 – 100 s.•Impact of μTD-tube dimensions on a.o. breakthrough, porosity and linear velocity.